Respuesta :

Answer:

Step-by-step explanation:

If you are going to graph this, then you should get everything to one side and equate the empty side to y

y = 6x^2 + 19x + 15

The graph is below.

You could use the quadratic equation on this, but it does factor, although not easily.

y = (3x +  5 )(2x +    3)

the roots are found by equating the two binomial factors to 0, each in turn.

3x + 5 = 0                   Binomial factor number one. equate to 0

3x = - 5                       Subtract 5 from both sides

3x/3 = - 5/3                Divide by 3

x = - 1.667   or

x = - 1.67

2x + 3 = 0                  Binomial factor number two. equate to 0

2x = - 3                      Subtract 3 from both sides

2x/2 = -3/2              

x = - 1.5

Ver imagen jcherry99
ACCESS MORE